2017
DOI: 10.1177/2050640616680971
|View full text |Cite
|
Sign up to set email alerts
|

Time trend occurrence of duodenal intraepithelial lymphocytosis and celiac disease in an open access endoscopic population

Abstract: Background: Duodenal intraepithelial lymphocytosis (DIL) is a histological finding characterized by the increase of intraepithelial CD3T-lymphocytes over the normal value without villous atrophy, mostly associated to coeliac disease (CD), Helicobacter pylori (Hp) gastritis and autoimmune diseases. Objective: To assess the occurrence of DIL, CD and Hp gastritis in an endoscopic population over a 13 year period. Methods: From 2003 to 2015 we included adult patients who consecutively underwent oesophago-gastro-du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…This is probably because the guidelines provide a strict endoscopic follow-up every 2–3 years [31], whereas for CeD there is no indication to repeat endoscopy, unless in the presence of onset or persistent symptoms [32]. Compared to previous literature, our results are similar to those described by Kalkan and Soykan [17] who identified 11 patients with CeD amongst 320 patients with AAG (3.4%) and higher than those of Galli et al [33] who described only 2 cases with histological evidence of AAG amongst 245 subjects with a new diagnosis of CeD. Therefore, evidence regarding the possible association with CeD has accumulated in recent years, but prospective studies are needed to confirm this hypothesis [1].…”
Section: Discussionsupporting
confidence: 85%
“…This is probably because the guidelines provide a strict endoscopic follow-up every 2–3 years [31], whereas for CeD there is no indication to repeat endoscopy, unless in the presence of onset or persistent symptoms [32]. Compared to previous literature, our results are similar to those described by Kalkan and Soykan [17] who identified 11 patients with CeD amongst 320 patients with AAG (3.4%) and higher than those of Galli et al [33] who described only 2 cases with histological evidence of AAG amongst 245 subjects with a new diagnosis of CeD. Therefore, evidence regarding the possible association with CeD has accumulated in recent years, but prospective studies are needed to confirm this hypothesis [1].…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, more recent studies have demonstrated the role of mast cells in GI functional disorders, such as IBS or functional dyspepsia, and the lack of their reduction after the beginning of a GFD [ 46 ]. In addition, some studies reported histological changes in the celiac stomach potentially responsible for the important prevalence of dyspepsia in CD patients at the time of diagnosis [ 46 , 47 , 48 , 49 ]. Although H.p.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is viewed as a quite common condition with an increasing trend over time. Galli et al [ 8 ] found the prevalence of ME to be 6.2% in a retrospective database of 7000 duodenal biopsy samples and, interestingly, reported a fivefold increase from 2010 to 2013, especially for non-gluten related disorders. Another two studies reported a prevalence of ME of 1.3% and 2.2%, respectively [ 9 , 10 ].…”
Section: Introduction: Definition Of Microscopic Enteritis (Me) and Ementioning
confidence: 99%